Environmental selection shapes the formation of near-surface groundwater microbiomes. (1st March 2020) - Yan, Lijuan; Herrmann, Martina; Kampe, Bernd; Lehmann, Robert; Totsche, Kai Uwe; Küsel, Kirsten
Abstract: Hydrodynamics drives both stochastic and deterministic community assembly in aquatic habitats, by translocating microbes across geographic barriers and generating changes in selective pressures. Thus, heterogeneity of hydrogeological settings and episodic surface inputs from recharge areas might play important roles in shaping and maintaining groundwater microbial communities. Here we took advantage of the Hainich Critical Zone Exploratory to disentangle mechanisms of groundwater microbiome differentiation via a three-year observation in a setting of mixed carbonate-siliciclastic alternations along a hillslope transect. Variation partitioning of all data elucidated significant roles of hydrochemistry (35.0%) and spatial distance (18.6%) but not of time in shaping groundwater microbiomes. Groundwater was dominated by rare species (99.6% of OTUs), accounting for 25.9% of total reads, whereas only 26 OTUs were identified as core species. The proximity to the recharge area gave prominence to high microbial diversity coinciding with high surface inputs. In downstream direction, the abundance of rare OTUs decreased whereas core OTUs abundance increased up to 47% suggesting increasing selection stress with a higher competition cost for colonization. In general, environmental selection was the key mechanism driving the spatial differentiation of groundwater microbiomes, with N-compounds and dissolved oxygen as the major determinants, but it was more prominent in the upper aquifer with low flow velocity. Across the lower aquifer with higher flow velocity, stochastic processes appeared to be additionally important for community assembly. Overall, this study highlights the impact of surface and subsurface conditions, as well as flow regime and related habitat accessibility, on groundwater microbiomes assembly. Graphical abstract: Image 1 Highlights: Hydrochemistry explains more microbial variations than spatial distance and time. Differences in flow velocity between aquifers shape the dominant assembly processes. N-compounds and dissolved oxygen are the major determinants. Proximity to the recharge area gave prominence to high microbial diversity. The abundance of the groundwater core OTUs increases in the downstream direction.